Infantile-Onset Isolated Neurohypophyseal Langerhans Cell Histiocytosis with Central Diabetes Insipidus: A Case Report - Mizuki Tani; Shota Hiroshima; Hidetoshi Sato; Kentaro Sawano; Yohei Ogawa; Masaru Imamura; Makoto Oishi; Keisuke Nagasaki (MDPI AG, 2022)
Central diabetes insipidus (CDI) is a rare disease in children and has a variety of etiologies. The major causes of CDI with pituitary stalk thickening (PST) are germinoma, Langerhans cell histiocytosis (LCH), and Lymphocytic infundibulo-neurohypophysitis, which are difficult to differentiate by imaging and require pathological diagnosis. We report a case of infantile-onset isolated neurohypophyseal LCH diagnosed by pathological findings. A 2-year-old girl presented with polydipsia and polyuria. CDI was diagnosed and treatment with oral desmopressin was initiated. Magnetic resonance imaging (MRI) of the head showed PST and absence of high-signal intensity of posterior pituitary on T1-weighted images. Follow-up MRI scans showed that the tumor mass was gradually increasing and extending posteriorly toward the area near the mamillary body. Simultaneously, anterior pituitary dysfunction was observed. She underwent a biopsy of the PST and LCH was diagnosed by immunohistochemical analysis. DNA analysis showed no BRAF V600E mutation. Monotherapy with 2-Chlorodeoxyadenosine reduced the tumor size but did not improve pituitary function. Isolated neurohypophyseal LCH should be considered in infantile-onset cases of CDI with PST. 2-CdA treatment resulted in rapid PST shrinkage. Further cases are needed to determine whether early diagnosis and treatment can prevent anterior pituitary dysfunction.